Association of Single Nucleotide Polymorphisms in a Disintegrin and Metalloproteinase 12 Gene With Susceptibility to Knee Osteoarthritis: A Meta-Analysis - Jae Hyun JUNG; Gwan Gyu SONG; Jae-Hoon KIM; Sung Jae CHOI (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the association between a disintegrin and metalloproteinase 12 polymorphisms and susceptibility to knee osteoarthritis (OA) through a meta-analysis involving only studies that present original data. Materials and methods: A meta-analysis was performed on the association between a disintegrin and metalloproteinase 12 rs3740199, rs1871054, rs1278279 and rs1044122 polymorphisms and knee OA. An electronic search of all relevant studies published up to January 2017 was conducted using MEDLINE and EMBASE. The study included six case-control studies including 2,966 patients (850 males, 2,116 females) with knee OA and 4,901 controls (2,286 males, 2,615 females). Results: No significant association was found between the rs3740199, rs1278279, and rs1044122 polymorphisms and knee OA when all studies were pooled into the meta-analysis. However, a significant association was found between the rs1871054 polymorphism and the knee OA risk (allele contrast: odds ratio (OR)=1.42, 95% confidence interval (CI)=1.02-1.98, p=0.04; dominant: OR=1.36, 95% CI=1.02-1.82, p=0.04; recessive: OR=1.83, 95% CI=1.14-2.94, p=0.01; and addictive model: OR=1.85, 95% CI=1.06-3.23, p=0.03). In the subgroup analysis, a significant association was found between the recessive (OR=0.44, 95% CI=0.21-0.93, p=0.03) and addictive model (OR=0.29, 95% CI=0.12–0.69, p<0.01) in the male group. Conclusion: Our meta-analysis suggests that the rs1871054 polymorphism is associated with susceptibility to knee OA and that the GG genotype of rs3740199 was associated with knee OA in the male group. Additional well-designed studies are required to confirm these results.